Atom-probe tomography of tribological boundary films resulting from boron-based oil additives. (15th January 2016) - Kim, Yoon-Jun; Baik, Sung-Il; Bertolucci-Coelho, Leonardo; Mazzaferro, Luca; Ramirez, Giovanni; Erdermir, Ali; Seidman, David N.
Graphical abstract: Abstract: Correlative characterization using atom-probe tomography (APT) and transmission electron microscopy (TEM) was performed on a tribofilm formed during sliding frictional testing with a fully formulated engine oil, which also contains a boron-based additive. The tribofilm formed is ∼15 nm thick and consists of oxides of iron and compounds of B, Ca, P, and S, which are present in the additive. This study provides strong evidence for boron being embedded in the tribofilm, which effectively reduces friction and wear losses.